2013
DOI: 10.1063/1.4813259
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between carrier localization and efficiency droop in AlGaN epilayers

Abstract: Photoluminescence studies of carrier dynamics in AlGaN epilayers with different degrees of carrier localization and densities of nonradiative recombination centers show that the prevailing droop mechanism in AlGaN epilayers with strong carrier localization and comparatively high density of nonradiative recombination centers is enhanced nonradiative recombination due to the carrier delocalization at elevated carrier density. The photoluminescence was investigated under quasi-steady-state excitation in the tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…The initial temperature of blue shift in AlGaN epilayers increases with localization parameter r raised. 23,24 In this study, no blue shift of exciton emission peak can be observed in the SnO 2 QDs with the temperature rise from 12 K to 300 K because of the very deep localized well that cannot be thermally activated below room temperature.…”
Section: Resultsmentioning
confidence: 57%
“…The initial temperature of blue shift in AlGaN epilayers increases with localization parameter r raised. 23,24 In this study, no blue shift of exciton emission peak can be observed in the SnO 2 QDs with the temperature rise from 12 K to 300 K because of the very deep localized well that cannot be thermally activated below room temperature.…”
Section: Resultsmentioning
confidence: 57%
“…At high currents, we have for the current noise density (5) Taking into account that S U = S J , we obtain for the spectral density of voltage fluctuations at high cur rents: (6) In diode C, at currents in the range of J = 0.1-1 mA where r j /r d = 1, n j ~ J 0.45 (Fig. 3, curve 3) and the cur rent noise grows as S J, meas ≈ S J ∝ J 1.45 (Fig.…”
Section: Hopping Transport In the Scr As A Source Of Excess 1/f Noisementioning
confidence: 99%
“…Alternative mech anisms primarily attribute this problem to defects in the material and to the design of the structure, i.e., to the degree of perfection of the fabrication technology. For example, the efficiency droop has been attributed to the increasing competition from nonradiative recombination at defects as a result of the full occu pancy of states in compositional fluctuations of the potential in an InGaN/GaN quantum well (QW) [2][3][4][5][6] or to slowing down of the lateral localization of injected carriers with increasing injection level [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is expected to be less pronounced in AlGaN due to the anticipated reduction of Auger coefficient, both direct and phonon-or impurity-assisted, with increasing band gap. 11,12 On the other hand, the connection between carrier localization and efficiency droop has been demonstrated in InGaN quantum well structures, 9,13,14 AlGaN epilayers, 15 and AlGaN quantum wells. 16 Recently, we proposed the ratio k B T/σ between the carrier thermal energy k B T and localization parameter σ (i.e.…”
mentioning
confidence: 99%
“…As the excitation is increased, an increasing fraction of carriers becomes delocalized, while only the deeper localized states remain filled-in. 15,16 The delocalized carriers can decrease the PL efficiency by the enhancement of nonradiative recombination as well as increase it due to bimolecular recombination, these two effects determined by the localization parameter σ. Due to the efficient thermal redistribution, higher carrier densities and, hence, excitation power densities are required to saturate the localized states and result in the efficiency droop via increased probability to reach the nonradiative recombination centers [see Fig.…”
mentioning
confidence: 99%